If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 35 + -11x = -4x Solving 35 + -11x = -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. 35 + -11x + 4x = -4x + 4x Combine like terms: -11x + 4x = -7x 35 + -7x = -4x + 4x Combine like terms: -4x + 4x = 0 35 + -7x = 0 Add '-35' to each side of the equation. 35 + -35 + -7x = 0 + -35 Combine like terms: 35 + -35 = 0 0 + -7x = 0 + -35 -7x = 0 + -35 Combine like terms: 0 + -35 = -35 -7x = -35 Divide each side by '-7'. x = 5 Simplifying x = 5
| f(6)=x^2-x+5 | | x^3+12x=100 | | 3+2i/4+3i | | x^6=665 | | 2a+4b-c+2d=-7 | | X+3/11-X-3/7=-2 | | -1/2y-4/5=-2/7 | | 11=((7y-1)/2)+((4y-5)/7) | | (-2x^2)-(18x)=0 | | (5x-3)(5x-9)= | | 12x^2+12x-26=0 | | c=54d-1/3b | | -2y=3-4x | | 5y=2x-9 | | 6x-12=4x+16 | | 10x+14y=5412 | | -y=1-6x | | 3(4c-1)-5=7c+7 | | 16r-8=14r+42 | | 6r=2r+6 | | y=90+0.8y | | 2y=6-3x | | x+19+3x=-33-3x-99 | | 20-47=5(x-1)-7 | | 3x(j-6)=176 | | f(-8)=7x+7 | | y=-4-5x | | -5y=15-6x | | 2y=12x+5 | | x-(6x-7)=2x-(5x+9) | | -3y+7x=23 | | -y=3-x |